ANALISIS SISTEM EVALUASI PROGRAM STUDI BERBASIS EVALUASI DIRI (EPSBED) DALAM MENINGKATKAN PELAYANAN KEPADA MAHASISWA PADA PROGRAM STUDI ADMINISTRASI NEGARA (Studi pada Fakultas Ilmu Sosial dan Ilmu Politik USBRJ) - Dewi, Lies Kumara; Rauf, Eka Ubaya Taruna (JURNAL SOSIAL DAN HUMANIS SAINS, 2017)
Evaluation System Based on Self Evaluation Study Program (EPSBED) is a tool for preparing reports of study programs. This application program is intended to facilitate universities in preparing EPSBED report including can be used by universities of Sang Bumi Ruwa University Jurai Bandar Lampung generally and Faculty of Social and Political Sciences Sang Earth Ruwa Jurai Bandar Lampung especially to archive student data. This study aims to determine the evaluation system of self-evaluation based study program and to know the service to students in the State Administration Program Faculty of Social and Political Sciences. This study uses qualitative research methods, with the aim of obtaining data. Based on the results of the research can be seen that EPSBED on State Administration Studies Program Faculty of Social and Political Sciences Sang Earth Ruwa Jurai University is User Friendly, in accordance with the needs of Higher Education, pressing Operational Costs, Web-based / Network. Then it is also known that EPSBED system can improve services to students in the State Administration Program Faculty of Social and Political Sciences such as a) Providing appropriate services. b) Provide fast service. c) Cheap, in the sense that students get what they want at a low cost. d) Provide friendly service.